Respuesta :

We multiply by "a" & "c" until we find the value of it for both problems!

1 ➡-4(a)-2(a)+11-6(a)-13=?
?=0

 -12(a) + 24  = ?

-12 = 0

a - 2 = 0
+2. +2
--- ----
2a. + 2

We have one solution in this problem!

Therefore, a = 2 would be your answer

-----------------------------------------------------------

2➡2(c)+4-3(c)-(-9+(c)+5)=?
? = 0

-2(c) + 8   

-2 = 0, right?

c - 4 = 0
+4 +4
--- ---
4c + 4

We have one solution in this problem as well

Therefore, c = 4 would be your answer